Harmonic sums and polylogarithms at non-positive multi-indices. (November 2017) - Duchamp, G.H.E.; Hoang Ngoc Minh, V.; Ngo, Quoc Hoan
Abstract: Extending Eulerian polynomials and Faulhaber's formula, 1 we study several combinatorial aspects of harmonic sums and polylogarithms at non-positive multi-indices as well as their structure. Our techniques are based on the combinatorics of noncommutative generating series in the shuffle Hopf algebras giving a global process to renormalize the divergent polyzetas at non-positive multi-indices.